Access to Photoreactive Core‐Shell Nanomaterials by Photoinitiated Polymerization‐Induced Self‐Assembly. Issue 11 (4th November 2019) - Molle, Edgar; Le, Dao; Norizadeh Abbariki, Tannaz; Akdemir, Meryem S.; Takamiya, Masanari; Miceli, Enrico; Kassel, Olivier; Delaittre, Guillaume
Abstract: We report the straightforward synthesis of photoreactive nanoobjects exhibiting various colloidal morphologies by photoinitiated polymerization‐induced self‐assembly (PISA). Poly(oligoethylene glycol methyl ether methacrylate) copolymers with pendent UV‐activatable diaryl tetrazole moieties were employed as macromolecular chain‐transfer agents in water for the dispersion photopolymerization of 2‐hydroxypropyl methacrylate under visible light. This led to the in situ formation of amphiphilic block copolymers, driving the self‐assembly into core‐shell nanoparticles, nanofibers, and nano/microvesicles. The tetrazole group present in the shell of the nanoobjects permitted functionalization with various functional molecules and polymers via UV‐triggered nitrile imine‐mediated tetrazole–ene cycloaddition (NITEC), enabling the alteration of surface properties of the nanomaterials (fluorescence, charge, hydrophilicity). Abstract : Keep it safe : Surface photoreactive core‐shell polymeric nanomaterials exhibiting various morphologies are obtained by photoinitiated reversible‐deactivation radical dispersion polymerization. Corresponding spherical nanoparticles and nanofibers exposing diaryl tetrazole moieties are then modified by phototriggered 1, 3‐dipolar cycloaddition with various enes.